Two new species from China of the Californian grass-living genus Prosopoanaphothrips (Thysanoptera, Thripinae) - Sun, Xinshuo; Huang, Datao; Li, Yaya; Dang, Lihong (Zootaxa, 2026)
The Californian grass-living genus Prosopoanaphothrips is newly recorded from China with two new species, P. flavipes sp. nov. from Aba, Sichuan and P. qilianshanensis sp. nov. from Qilian, Qinghai. These two are distinguished from the type species, P. reticulatus, by antennal segment IV with a forked sense cone.